Magnetoelectrical Clothing Generator for High‐Performance Transduction from Biomechanical Energy to Electricity (Adv. Funct. Mater. 6/2022). (2nd February 2022) - Wang, Rui; Du, Zhuolin; Xia, Zhigang; Liu, Jiaxin; Li, Pan; Wu, Zhenhua; Yue, Yamei; Xiang, Yuanzhuo; Meng, Jinchang; Liu, Dexiang; Xu, Weilin; Tao, Xiaoming; et al.
Abstract : Magnetoelectrical Clothing Generator In article number 2107682, Weilin Xu, Xiaoming Tao, Guangming Tao, Bin Su, and co‐workers show scalable‐manufactured flexible magnetoelectrical clothing that can convert mechanical energy generated by daily behavior into electrical energy required for electronic devices, solving the problem of continuous power supply of electronic clothing especially in harsh outdoor environments, and promoting sustainable development in wearable electronics.